AI-Driven 3D Reconstruction and Annulus Measurement for TAVR Planning - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Discover how AI-powered 3D reconstruction and annulus measurements improve TAVR planning, valve sizing, and reduce complications like paravalvular leak.
Keywords: TAVR; Artificial Intelligence; 3D Reconstruction; Annulus Measurement; Cardiology